2018
DOI: 10.1021/acssynbio.7b00390
|View full text |Cite
|
Sign up to set email alerts
|

Modular Engineering Intracellular NADH Regeneration Boosts Extracellular Electron Transfer of Shewanella oneidensis MR-1

Abstract: Efficient extracellular electron transfer (EET) of exoelectrogens is essentially for practical applications of versatile bioelectrochemical systems. Intracellular electrons flow from NADH to extracellular electron acceptors via EET pathways. However, it was yet established how the manipulation of intracellular NADH impacted the EET efficiency. Strengthening NADH regeneration from NAD, as a feasible approach for cofactor engineering, has been used in regulating the intracellular NADH pool and the redox state (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(49 citation statements)
references
References 82 publications
3
46
0
Order By: Relevance
“…For example, it was necessary to eliminate pathways that compete for NADH in E. coli to improve 1-butanol production (Atsumi et al, 2008). Increasing NADH generation has also been used to enhance electric current production by S. oneidensis MR-1 (Li et al, 2018). These studies show the importance of NADH availability when engineering redox cofactor-dependent pathways.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it was necessary to eliminate pathways that compete for NADH in E. coli to improve 1-butanol production (Atsumi et al, 2008). Increasing NADH generation has also been used to enhance electric current production by S. oneidensis MR-1 (Li et al, 2018). These studies show the importance of NADH availability when engineering redox cofactor-dependent pathways.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies, the electron mediators-mediated extracellular electron transport mechanism is a circulation mechanism. The oxidized mediators are converted into the reduced mediators after being coupled intracellularly with the reduction products on the respiratory chain [33]. Then reduced mediators are discharged out of the extracellular, and the electrons are transferred to the electrode to be oxidized.…”
Section: Effect Of Electron Mediators On Electricity Generation Perfomentioning
confidence: 99%
“…EET mechanism of EAB in MFCs can be summarized as follows: Intracellular electrons are transferred from the quinone pool on the inner membrane to the outside of the cell through the periplasm and outer membrane, during which it passes through a series of transmembrane cytochrome complexes. Electrons pass directly to the anode, which is the rst EET mechanism [9]. The second EET mechanism is that after the electrons pass through the transmembrane cytochrome complex, the electrons are not directly transferred to the anode, but are transferred to the anode through conductive pilus, that is, nanowires [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Fdn in MR-1 is a homologue of nitrate-inducible formate dehydrogenase FDH-N in Escherichia coli (Jormakka et al 2002), suggesting that nitrate reduction would induce the expression of fdnGHI. MR-1 may also have an NAD-dependent formate dehydrogenase (SO_3922), while it has been reported that this gene does not significantly affect catabolism in MR-1 (Li et al 2018a). However, it has also been described that the introduction of NAD-dependent FDH in Moraxella sp.…”
Section: Catabolic and Electron-transport Pathwaysmentioning
confidence: 99%